Kosteneffizienter und effektiver Biodiversitätsschutz durch Ausschreibungen und eine ergebnisorientierte Honorierung: das Modellprojekt Blühendes Steinburg - Markus Groth (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
Against the background of a rapid biodiversity loss in agricultural landscapes, increasing attention is being paid to farming practices that enhance ecosystem services. Therefore developing a cost-efficient and effective conservation-compatible land use policy to influence private land management is the main challenge facing present European agri-environmental policy. This paper deals with the design, implementation and results of a case-study payment scheme in the county Steinburg in the northernmost federal state of Germany (Schleswig-Holstein). The payment scheme combines a payment-by-results approach and the use of conservation procurement auctions in order to improve the cost-effectiveness of conservation schemes for grassland plant biodiversity.
Keywords: C93; D44; H41; Q24; Q28; Q57; R52; 330; Agrarumweltprogramme; Ausschreibungen; ergebnisorientierte Honorierung; experimentelle Ökonomik; Informationsasymmetrie; Ökosystemdienstleistungen; pflanzliche Biodiversität; Vertragsdifferenzierung; Vertragsnaturschutz